Strategic selection of MDM2 inhibitors enhances the efficacy of FAK inhibition in mesothelioma based on TP53 genotype - Xuerao Ning; Thảo Thi Thanh Nguyễn; Takao Morinaga; Yuji Tada; Hideaki Shimada; Kenzo Hiroshima; Naoto Yamaguchi; Masatoshi Tagawa (PLoS ONE, 2026)
Mesothelioma has characteristic genetic changes including inactivation of neurofibromatosis type 2 ( NF2 ) and deletion of the INK4A/ARF region. Cells deficient of NF2 protein (MERLIN) depend on focal adhesion kinase (FAK) for cell adhesion and FAK inhibitors suppress the cell growth. The INK4A/ARF deletion activates MDM2 functions which ubiquitinate and degrade p53, and consequently the cellular p53 levels decrease. The deletion therefore induces loss of p53 functions although a majority of mesothelioma has wild-type TP53 genotype. An MDM2 inhibitor which blocked the ubiquitination increased p53 levels, restored p53 functions and facilitated cell growth arrest. Moreover, FAK and p53 expressions were reciprocally regulated. We examined growth suppressive effects of a FAK inhibitor, defactinib, and MDM2 inhibitors, nutlin-3a and reactivation of p53 and induction of tumor cell apoptosis (RITA), with representative wild-type and mutated TP53 mesothelioma and investigated molecular changes induced by the agents. We analyzed possible combinatory effects of the inhibitors and molecular changes caused by the combination. Our study showed that defactinib inhibited cell growth and induced FAK dephosphorylation irrespective of the TP53 genotype, and that the inhibited FAK phosphorylation was not associated with MERLIN levels or with p53 up-regulation, but linked with AKT dephosphorylation. Nutlin-3a preferentially suppressed growth of wild-type TP53 cells and augment p53 expression without DNA damage, whereas RITA-mediated p53 up-regulation was linked with the damage. A combination of defactinib and the MDM2 inhibitors showed that nutlin-3a showed synergistic/additive effects in wild-type and antagonistic effects in mutated TP53 cells, whereas RITA retained synergistic activity in mutated TP53 cells. These results suggest that the therapeutic success of combined FAK and MDM2 inhibition in mesothelioma depends on the precise matching of MDM2 inhibitors with the TP53 genotypes, and highlight the need for genotype-based selection of MDM2 inhibitors.